KEMAHIRAN BAHASA INGGRIS DAN KOMPETENSI BUDAYA UNTUK PROFESIONAL PARIWISATA DI INDUSTRI PARIWISATA GLOBAL - I Gede Astawa; Eka Anastasia Wijaya (Jurnal Kajian dan Terapan Pariwisata, 2024)
As the travel and tourism industry becomes increasingly globalized, the ability to communicate effectively in English has become critical for professionals working in the sector. While previous research has established the importance of English language proficiency, questions remain regarding best practices for skills development. This study aims to explore the role of English proficiency for tourism professionals in the current era of globalization. Specifically, it examines strategies for improving language skills and considers the necessity of cultural competence training. A literature review was conducted analyzing peer-reviewed research on English language training programs, cultural awareness development, and the impacts of communication competencies. Gaps in existing knowledge were identified regarding training evaluation, longitudinal proficiency impacts, and links to business outcomes. The results of the study found that English functions as the lingua franca facilitating interactions between diverse travelers. Proficiency allows professionals to serve customers while cultural competence fosters understanding. Specialized training focusing on skills and sensitizing professionals is important. However, research on specific method efficacies, integrating cultural awareness, varied contexts, and proficiency-performance relationships remains limited. This study conclude that English proficiency and cultural competence are essential for tourism professionals in today's global environment. While their value is established, further empirical study of training best practices, longitudinal impacts, and relationships to tangible outcomes is warranted. Addressing gaps can optimize skills development approaches and business performance.